2021
DOI: 10.1089/end.2020.0567
|View full text |Cite
|
Sign up to set email alerts
|

A Modified Endoscopic Primary Realignment of Severe Bulbar Urethral Injury

Abstract: Purpose: Male urethral injury is a common urologic emergency in developing countries. Whether early or late treatment of urethral injuries is often multifactorial and controversial. The goal of this study is to determine whether early realignment can reduce postsurgical complications and evaluate the clinical feasibility of emergency endoscopic urethroplasty using single rigid ureteroscopy in the treatment of bulbar urethral severe injury. Patients and Methods: Between September 2013 and March 2019, 15 male ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…They concluded that while PER may result in the restoration of urethral continuity without the need for further intervention, PER patients may require multiple interventions and experience more adverse events than SPT patients. Zhang et al [ 6 ] reported a modified procedure involving the use of standard semi-rigid ureteroscopy to reduce manipulation-related trauma, which resulted in a good success rate and a low subsequent comorbidity rate. However, the suprapubic route was established by means of serial sheath dilatations and then completed using a 16-Fr peel-away sheath.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They concluded that while PER may result in the restoration of urethral continuity without the need for further intervention, PER patients may require multiple interventions and experience more adverse events than SPT patients. Zhang et al [ 6 ] reported a modified procedure involving the use of standard semi-rigid ureteroscopy to reduce manipulation-related trauma, which resulted in a good success rate and a low subsequent comorbidity rate. However, the suprapubic route was established by means of serial sheath dilatations and then completed using a 16-Fr peel-away sheath.…”
Section: Discussionmentioning
confidence: 99%
“…In an effort to increase the success rate of PER, one retrospective study suggested performing antegrade realignment via the suprapubic tract using semi-rigid ureteroscopy[ 6 ]. However, this technique requires the use of a unique peel-away sheath to establish a suprapubic tract, which is not currently widely accessible.…”
Section: Introductionmentioning
confidence: 99%
“…Since urethral wounds are infrequent, their occurrence has already been growing due to an increase in the number of highway vehicle accidents [ 50 ]. The preponderance of urethral injuries can be caused by either blunt trauma to the abdominal (typically coupled with a pelvic fracture) or straddling damage to the pelvis [ 38 ].…”
Section: Introductionmentioning
confidence: 99%
“…Most patients seek medical attention immediately or within a few days after by visiting a physician. Additionally, while chronic retention of foreign bodies in the bladder and urethra does occur, these cases that tend to lead to renal failure have been rarely reported, and only a few involved sexual function (Bedke et al, 2010;Singh, 2007;Zhang et al, 2021). There are limited data about sexual function and its relationship with chronic foreign body retention in the LUT.…”
mentioning
confidence: 99%